PENGARUH CITRA MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA SEHAT BAKERY SIBULUAN INDAH - Waruwu, Otomosi; Ambarita, Rosmita; Hasibuan, Nur’ainun (Lembaga Pengembangan Kinerja Dosen, 2023)
The formulation of the problem in this study is whether brand image and promotion influence consumer purchasing decisions at Sehat Bakery Sibuluan Indah? The purpose of this study was to find out and analyze the influence of brand image and promotion on consumer purchasing decisions at Sehat Bakery Sibuluan Indah. The hypothesis in this study is brand image and promotion have a positive effect on consumer purchasing decisions at Sehat Bakery Sibuluan Indah. population of 250 people. The sample is 63 people. Data sources come from primary and secondary data. The research results show that the coefficient of determination R Square is 56.4%. Simultaneous testing obtained Fcount (38.829) greater than Ftable (3.15) or (38.829 > 3.15) meaning that brand image and promotion together have a positive effect on consumer purchasing decisions. Brand image variable has a positive and significant effect on purchasing decisions consumers where the t-count value is 2.738 > the t-table value is 1.999. Partially the promotion variable has the most dominant influence on consumer purchasing decisions, where the t-count value is 5.703 > ttable 1.999